Before Boas the genesis of ethnography and ethnology in the German enlightenment - Vermeulen, Han F. 1952- (Critical Studies in the History of Anthropology, 2015)
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Preface -- Acknowledgments -- Series Editors' Introduction -- 1. History and Theory of Anthropology and Ethnology -- 2. Theory and Practice -- 3. Enlightenment and Pietism -- 4. Ethnography and Empire -- 5. Anthropology and the Orient -- 6. From the Field to the Study -- 7. Anthropology in the German Enlightenment -- 8. Epilogue -- Conclusion -- Notes -- References Cited -- Index.